Comparative Analysis of Three Different Negative Emission Technologies: BECCS, Absorption and Adsorption of Atmospheric CO2 - Talei, Saeed; Soleimani, Zahra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Negative Emission Technologies (NETs) are generally considered as vital methods for achieving climate goals. To limit the rise in the global average temperature below 2°C, a large number of countries that participated in the Paris agreement was virtually unanimous about the effective collaboration among members for the reduction of CO2 emissions throughout this century.
Keywords: negative emission technology; climate changes; BECCS; absorption; adsorption; CO2; Paris agreement; technologie negatywnej emisji; zmiany klimatu; wchłanianie; adsorpcja; porozumienie paryskie